2019
DOI: 10.1002/sctm.18-0212
|View full text |Cite
|
Sign up to set email alerts
|

Fructose 1,6-Bisphosphate as a Protective Agent for Experimental Fat Grafting

Abstract: Fat grafting procedures are considered to be a promising regenerative, cell‐directed therapy; however, their survival is mainly influenced by ischemia condition. Fructose 1,6‐bisphosphate (FBP), as an intermediate in energy metabolism, has the potential to rescue cells and tissues from hypoxic‐ischemic circumstances. In the present study, human lipoaspirates were grafted subcutaneously into nude mice followed by a daily intraperitoneal injection of FBP at different doses for 7 days. Next, the grafts were harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…shown multiple protective properties including anti-fibrotic, antiinflammatory, anti-convulsant, and immunomodulatory effects. 114 Being the first rate-limiting enzymes in the glycolytic pathway, PFK1…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…shown multiple protective properties including anti-fibrotic, antiinflammatory, anti-convulsant, and immunomodulatory effects. 114 Being the first rate-limiting enzymes in the glycolytic pathway, PFK1…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…This specific metabolic milieu may influence macrophage function indirectly. Fructose‐1,6‐bisphosphate (FBP), an endogenous intracellular metabolite in the glycolytic pathway produced by phosphofructokinase‐1 (PFK1), has shown multiple protective properties including anti‐fibrotic, anti‐inflammatory, anti‐convulsant, and immunomodulatory effects 114 . Being the first rate‐limiting enzymes in the glycolytic pathway, PFK1 would catalyze the phosphorylation of fructose‐6‐phosphate (F‐6‐P) to fructose 1,6‐bisphosphate (F‐1,6‐2P) using adenosine triphosphate (ATP), whereas fructose bisphosphatase‐1 (FBP1) would mediate the conversion of F‐1,6‐2P into F‐6‐P in the gluconeogenic pathway.…”
Section: Decidual Macrophagesmentioning
confidence: 99%
“…[27][28][29][30] Previous research has demonstrated the benefits of FBP for treating ischemia myocardia, promoting the survival of transplanted adipose tissue, maintaining bone homeostasis, and safeguarding hypoxia reperfusion ECs. [31][32][33][34][35][36] Therefore, it is a more efficient option to use high-energy intermediate FBP to directly supply energy to damaged tissue cells. However, FBP was originally administered intravenously in huge dosages without any targeting, which may lead to lactic acid poisoning, increased uric acid and other risks, and even life-threatening, and it is also challenging to maintain effective concentration when used locally.…”
Section: Introductionmentioning
confidence: 99%
“…Before neovascularization develops, the graft must face a period of hypoxia, so other researchers thought that the resilience of adipocytes to hypoxia and relative macrophage activation play crucial roles in fat graft retention. 11 , 12 , 13 Adipocytes are sensitive to stress and hypoxia, which are the two major obstacles in large‐volume fat grafting. 14 Researchers found that apoptosis induced by many factors in the graft environment such as hypoxia and inflammation is a cause of long‐term volume reduction of the fat graft.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these methods have limited effects in improving the survival of transplanted fat and cannot be used in clinical applications. Before neovascularization develops, the graft must face a period of hypoxia, so other researchers thought that the resilience of adipocytes to hypoxia and relative macrophage activation play crucial roles in fat graft retention 11–13 . Adipocytes are sensitive to stress and hypoxia, which are the two major obstacles in large‐volume fat grafting 14 .…”
Section: Introductionmentioning
confidence: 99%